Agricultural investment for growth and poverty reduction in Nigeria - Alpuerto, Vida; Diao, Xinshen; Salau, Sheu; Nwafor, Manson (International Food Policy Research Institute, 2009)
This study assesses public investment required for agricultural growth and poverty reduction in Nigeria. Using time series data for public spending and agricultural total factor productivity (TFP) growth, the econometrically estimated results show that one percent of growth in agricultural spending generates 0.24 percent of growth in agricultural TFP. To support 9.5 percent in agricultural annual growth in 2009-17, a growth rate from the economy-wide analysis on options of growth for poverty reduction (Diao et al. 2009), required agricultural investment would have to grow at 23.8 percent annually in the same period. However, if the spending efficiency were improved based on an estimated elasticity for Sub-Saharan Africa as whole, then required agricultural investment would grow at 13.6 percent per year instead. The study also shows that investment outside agriculture benefits the agricultural sector. By taking into account such indirect effect of public investment, required growth in agricultural spending is much lower.